Visitors attitudes towards giant panda conservation programme in Zoo Negara, Malaysia - Ashaari, Afiq Akmal; Johari, Shazali (Taylor's University, 2016)
This paper describes the attitudes of visitors who visit the Giant Panda Conservation Centre (GPCC) in Zoo Negara, Hulu Kelang, Selangor. As the GPCC is still relatively new, there has not been many studies conducted on this place. Based on statistics from Zoo Negara, the increasing number of visitors who have visited the GPCC reflects a positive attitude towards this program. On the other hand, some Malaysians have expressed their dissatisfaction at the high cost of the GPCC. This situation has created a negative attitude towards the programme. The attitudes of visitors may vary according to socio-demographic factors like educational background and income. The focal point is to determine visitors' attitudes towards the giant panda conservation programme and also the relationship between the socio-demographic factors of visitors and their attitudes. The conservation programme for the giant pandas is one of the biggest that have been carried out in Malaysia so far. For the first time, a conservation programme for a wildlife species from China is being done in Malaysia. Hence, it is necessary to determine if the attitudes of visitors will be positive or negative. The outcome revealed that most of the visitors show a positive attitude through concern that this species is threatened by extinction. Also, most visitors support the conservation initiative for this endangered species. The outcome also revealed that some socio-demographic factors of the visitors such as age, income, ethnicity, gender and education level has a relationship with their attitudes.